Study on the Productive and Reproductive Performances of BLRI-1 and BLRI-2 Ducks in Bangladesh (The Agriculturists, 2014)
A total of 887 ducklings of BLRI-1 duck genotype and 352 ducklings of BLRI-2 duck genotype were studied to measure productive and reproductive performances under intensive management. Data were recorded on body weight, egg production, egg weight, fertility, embryonic mortality, hatchability, feed intake, age at sexual maturity, body weight at maturity and egg weight at maturity. The fertility rate in BLRI-1duck was significantly (p